Hydroxyethyl starch 6%, 130/0.4 vs. a balanced crystalloid solution in cardiopulmonary bypass priming: a randomized, prospective study - Gurbuz, Hasan Alper (BioMed Central, 2013)
BACKGROUND: Since the advent of cardiopulmonary bypass, many efforts have been made to avoid the complications related with it. Any component of the pump participates in occurrence of these adverse events, one of which is the type of prime solution. In this study, we aimed to compare the effects of 6% hydroxyethyl starch 130/0.4 with a commonly used balanced electrolyte solution on postoperative outcomes following coronary bypass surgery. METHODS: Two hundred patients undergoing elective coronary bypass surgery were prospectively studied. The patients were randomized in to two groups. First group received a balanced electrolyte solution and the second group received 6% hydoxyethyl starch 130/0.4 as prime solution. The postoperative outcomes of the patients were studied. RESULTS: The mean age of the patients was 61.81 ± 10.12 in the crystalloid group whereas 61.52 ± 9.29 in the HES group. There were 77 male patients in crystalloid group and 74 in HES group. 6% hydroxyethyl starch 130/0.4 did not have any detrimental effects on renal and pulmonary functions. The intensive care unit stay and postoperative hospital length of stay were shorter in hydroxyethyl starch group (p < 0.05 for each). Hydroxyethyl starch did not increase postoperative blood loss, amount of blood and fresh frozen plasma used, but it decreased platelet concentrate requirement. It did not have any effect on occurrence of post-coronary bypass atrial fibrillation (p > 0.05). CONCLUSIONS: 6% hydroxyethyl starch 130/0.4 when used as a prime solution did not adversely affect postoperative outcomes including renal functions and postoperative blood transfusion following coronary bypass surgery.